Professional development in strength and conditioning coaching through informal mentorship: A practical pedagogical guide for practitioners - Grant, M.; Dorgo, S.; Griffin, M. (Strength and Conditioning Journal, 2014)
Recent sport and strength and conditioning (sc) coaching literature has suggested the implementation of mentoring within a formal educational setting due to its recognized influence upon professional development, especially early in a career. However, informal mentoring, occurring outside a structured curricular program, has been an ongoing practice for many coaches entering the profession. An sc coach seeking a mentoring relationship would be hard pressed to locate developmental literature to guide the establishment. Therefore, the current article seeks to supply practical guidelines, based upon sport and sc coaching literature, to assist coaches in establishing an effective informal mentoring relationship.